The entrepreneurial nursing care inducing healthy practices in vulnerable communities - Dirce Stein Backes; Nathalia Hoffmann Adames; Amanda Schneider Weissheimer; Andreas Büscher; Marli Terezinha Stein Backes; Alacoque Lorenzini Erdmann (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To understand the meaning of entrepreneurial nursing care as inducer of healthy practices in vulnerable communities. Method: Grounded theory, whose data collection took place between March and December 2019, from interviews with 19 participants from the central region of Rio Grande do Sul, Brazil and comparative data analysis. Results: The phenomenon was delimited: Experiencing small/big transformations in the invisibility of everyday life in promoting healthy practices in vulnerable communities. Conducted by the paradigmatic model, the categories were named based on the components: Condition: Making choices and negotiating non-negotiable exchanges; Action/interaction: Motivating oneself to maintain basic human needs; Consequence: Broadening perspectives and transcending personal and collective boundaries. Conclusion: Entrepreneurial nursing care as inducer of healthy practices in vulnerable communities is not reduced to a scientific theory or to the linear and decontextualized apprehension of healthy living, but extends to reach small/big transformations that occur in the invisibility of everyday life.